Neo-elitism and counterterrorism operations in Kenya. Issue 1 (2nd January 2017) - Mwangi, Oscar Gakuo
ABSTRACT: Counterterrorism operations in Kenya have often been hindered by a lack of collaboration, coordination and cooperation among the security agencies involved in such operations. This article examines the relationship between neo-elitism and counterterrorism security interagency activity in Kenya. Using neo-elitism as a framework for analysis, with specific reference to the September 2013 Westgate Mall attack counterterrorism operation, it is argued that the lack of collaboration, coordination and cooperation among Kenya's counterterrorism security agencies often results in unintended adverse consequences. The interagency conflict over the Westgate operation was primarily about command and control, intelligence sharing and official information shared with the public pertaining to the stages of the siege and operation. These security agencies share similar responsibilities and jurisdictions in the rest of the country's counterterrorism efforts. The interagency conflicts reveal that the country's security elites pursue personal and agency-specific interests that are aimed at maintaining organisational supremacy over counterterrorism efforts. Recommendations are offered for how to tackle the problem of interagency conflict in order to enhance the effectiveness of counterterrorism operations in Kenya.